2007
DOI: 10.1590/s0100-879x2006005000149
|View full text |Cite
|
Sign up to set email alerts
|

Early life, current socioeconomic position and serum lipids in young adulthood of participants in a cohort study initiated in 1978/1979

Abstract: The association between socioeconomic position (SEP) and serum lipids has been little studied and the results have been controversial. A total of 2063 young adults born in 1978/79 were evaluated at 23-25 years of age in the fourth follow-up of a cohort study carried out in Ribeirão Preto, SP, Brazil, corresponding to 31.8% of the original sample. Total serum cholesterol (TC), triglycerides, high-density cholesterol (HDL cholesterol) and low-density cholesterol (LDL cholesterol) were analyzed according to SEP a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
6
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 22 publications
1
6
0
Order By: Relevance
“…In our study, significantly higher HDL concentrations were recorded in children and adolescents with higher social status, meaning that children with lower social status would be exposed to a higher cardiovascular risk . This behaviour has been confirmed by other studies . Based on the mean statistics, we recorded effect sizes of 0.13 mmol/L, equivalent to 5.03 mg/dL, among boys and 0.29 mmol/L (11.21 mg/dL) in girls in the upper class compared to the lower class.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…In our study, significantly higher HDL concentrations were recorded in children and adolescents with higher social status, meaning that children with lower social status would be exposed to a higher cardiovascular risk . This behaviour has been confirmed by other studies . Based on the mean statistics, we recorded effect sizes of 0.13 mmol/L, equivalent to 5.03 mg/dL, among boys and 0.29 mmol/L (11.21 mg/dL) in girls in the upper class compared to the lower class.…”
Section: Discussionsupporting
confidence: 88%
“…In our study, no significant correlations between total cholesterol or LDL cholesterol and social class or family wealth could be detected. However, a study from Brazil, which only included young adults aged 23–25, found that social class had a significant (p < 0.05) influence on total cholesterol and LDL and HDL cholesterol: a low socioeconomic status was associated with lower concentrations . Thus, total cholesterol and LDL cholesterol represented more cardio‐protective factors for individuals of lower social classes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It was suggested that triglycerides level was inversely associated with education and salary in some developed areas 34,35 . However, other studies found that individuals of lower socioeconomic status (SES) had lower levels of TC and LDL-C in developing areas 36,37 . In our study, only-child families were characterized as higher in SES and OC had higher levels of TC and LDL-C, which were consistent with findings in developing areas, indicating greater CVD risks among OC.…”
Section: Discussionmentioning
confidence: 98%
“…This contrast of geographical location is important: in keeping with many other countries (3), a North-South divide in socioeconomic circumstances and, therefore health, exists in Brazil. The topics covered in this raft of reports vary and include predictors of perinatal health and maternal risk factors (4-7); early life determinants of cardiovascular risk factors (e.g., dyslipidemia) in childhood and adolescence (8)(9)(10)(11); use of health services (12), and a description of dietary characteristics of young adults (13), amongst other topics (14). There is also a guide to the background, objectives, sampling, and methodologies employed across these studies (15), which, together with similar pieces published in past issues of the Brazilian Journal (16), serve as a very useful starting point, particularly for potential collaborators.…”
mentioning
confidence: 99%